Analisis Struktural Puisi Sendiri Karya Abdul Hadi W.M. - Aziza Aulia Azzahra (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2022)
This study aims to describe the physical structure and inner structure of the poetry contained in the collection of poems by Abdul Hadi W.M. The method used is descriptive in the form of qualitative. The approach used is structural analysis. Based on the results of the study, it was found several things related to the physical structure, namely, the Poetry of the Self by Abdul Hadi W.M. using a physical structure. In the inner structure his feelings show a sense of loneliness. The tone or attitude that is shown through straightforward words is anger. The message does not have to vent emotions by harming others, we can be alone to calm the mind.